An Unexpected Case of Malignant Mesothelioma in a Young Woman. (February 2021) - Dhamrah, Umaima; Solomon, Nadia; Osuoji, Olive C.
A 41-year-old female with a past medical history significant only for right retinal vein occlusion presented with chest pain, cough, and shortness of breath. After being found to have a large right-sided pleural effusion and undergoing a nondiagnostic thoracentesis, a noncontrast chest computed tomography scan revealed multiple diffuse nodules in the right lung with irregular paraspinal pleural thickening. An extensive workup followed, with computed tomography–guided biopsy ultimately revealing the diagnosis. The following report describes the patient presentation, laboratory findings, and extensive clinical investigation, and provides a discussion of the epidemiology, imaging findings, prognosis, and differential diagnoses for the illness in question.